THE IMPACT OF ISLAMIC FINTECH ON THE SUSTAINABLE ECONOMY: CASE STUDY AND IMPLICATIONS - Amalia, Alfi; Afandi, Ahmad; Hayati, Isra; Lubis, Andrew Satria (Proceeding International Seminar of Islamic Studies, 2024)
Broad and sustainable financial inclusion has become the main goal in efforts to improve the welfare of society in the Muslim world. This article explains how Sharia Fintech has overcome some traditional barriers in access to financial services, such as geographical distance, limited financial infrastructure, and obstacles to compliance with sharia principles. This study also evaluates the positive impact of Sharia Fintech in increasing financial inclusion, reducing economic inequality, and supporting economic growth in countries with a majority Muslim population. The results of this research provide a better understanding of the potential of Sharia Fintech in creating a more inclusive and sustainable financial system in the Muslim world, and illustrate how technology can be a powerful tool to achieve these goals.